2007
DOI: 10.1111/j.1744-313x.2007.00712.x
|View full text |Cite
|
Sign up to set email alerts
|

The interleukin‐6 (IL6)–174 G/C promoter genotype is associated with the presence of septic shock and the ex vivo secretion of IL6

Abstract: Septic shock is associated with a high mortality and an excessive activation of immune cascades. Interleukin (IL)-6 has been found to be a key cytokine in the pathogenesis of severe sepsis, but the importance of a regulatory polymorphism within the IL6 promoter has been controversial in these patients. The aim of the study was therefore to systematically investigate the IL6-174 G/C promoter genotype with regard to the presence of shock in patients with sepsis, the IL6 serum levels, and the ex vivo secretion of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
30
2
3

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 26 publications
(31 reference statements)
4
30
2
3
Order By: Relevance
“…There are few studies on recurrent infections, thrombophilia and immunological alterations, such as celiac disease, breast cancer, systemic lupus erythromatosus and leishmaniasis [15,[24][25][26]. Our study revealed that CC genotype of IL-6-G174C is more prevalent in the INS patient, and steroid resistant group, hence may be considered responsible for progression as well as for steroid resistance.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…There are few studies on recurrent infections, thrombophilia and immunological alterations, such as celiac disease, breast cancer, systemic lupus erythromatosus and leishmaniasis [15,[24][25][26]. Our study revealed that CC genotype of IL-6-G174C is more prevalent in the INS patient, and steroid resistant group, hence may be considered responsible for progression as well as for steroid resistance.…”
Section: Discussionmentioning
confidence: 61%
“…1a, b and c) in accordance with Tischendorf et al [15], Kobayashi et al [16] and Wilson et al [17]. To improve the genotyping quality and validation, Random samples were reanalyzed, in a double blind manner to confirm the RFLP results.…”
Section: Blood Collection and Dna Extractionmentioning
confidence: 99%
“…Tischendorf [19] demonstrated that a significantly lower frequency of the IL6-174 G/G genotype was associated with higher mortality in septic patients compared to surviving septic patients, that mean carriage the C allele put individuals at risk [19].…”
Section: Discussionmentioning
confidence: 99%
“…A common polymorphism located at position -174 in the promoter region is a G to C substitution, and in vitro studies demonstrate an association of the G allele with increased expression of IL-6 [139]. In addition, serum levels of IL-6 are lower in adults with sepsis with the C allele [140] and in healthy adults, the G allele is associated with higher basal serum levels of IL-6 [139]. In contrast, monocytes isolated from neonates with the C allele and stimulated with LPS produce more IL-6 than monocytes isolated from neonates with the G allele [141], the opposite of what is observed in adults.…”
Section: Interleukin 6 (Il-6)mentioning
confidence: 99%
“…A significantly lower frequency of the -174 GG genotype is associated with higher mortality in septic patients compared with surviving septic patients, suggesting that the GG genotype is in some fashion protective, or conversely carriage the C allele places individuals at risk. Indeed, in cohort of adult septic patients, the CC genotype was more frequent in those with shock [140]. Other SNPs also exist in the gene coding for IL-6 allowing for the analysis of haplotypes or combinations of various SNPs.…”
Section: Interleukin 6 (Il-6)mentioning
confidence: 99%